A case of severe optic neuropathy caused by biopsy proven cll without peripheral transformation with excellent treatment response to rituximab, obinutuzumab (second generation anti-cd20 monoclonal antibody) and chlorambucil. Issue 5 (8th May 2017) - Jhaveri, Divita; Swayne, Andrew; Brown, Helen; Airey, Caroline
Abstract : Objectives: This report is of a case of optic neuropathy caused by chronic lymphocytic leukaemia (CLL) seen at a tertiary neurology centre, a presentation that has been only rarely reported. The case also addresses the role of biological agents in the treatment of atypical neoplastic presentations. Case: A 59 year old female presents with two month history of blurred vision, severe bilateral papilloedema and rapid progression to blindness against a past medical history of CLL and chronic demyelinating peripheral neuropathy consistent with CIDP. The patient had experienced an indolent course with CLL never requiring treatment but CIDP did require chronic immunosuppression. A MRI scan of the brain with contrast revealed multiple enhancing cranial nerves and patches of meningeal enhancement. Lumbar puncture results included a raised opening pressure, a raised protein of 2 g/L but a normal white cell count. The diagnosis was made on biopsy of the dura which revealed CLL/small lymphocyte populations confirming the diagnosis of infiltration by CLL, despite no definite transformation evident in the blood at the time. Treatment with rituximab, obinutuzumab and chlorambucil led to a marked clinical recovery of vision as well as improvement in the peripheral neuropathy symptoms. Conclusions: This case illustrates that CLL can transform and cause atypical neurological sequelae without evidence of raised peripheral white cell count. The profound treatment response supports the use of biological agents in similar clinical contexts and raises the possibility that the demyelinating peripheral neuropathy may be a further atypical paraneoplastic phenomenon.